Efficiency enhancement of solution processed organic light emitting diodes (OLEDs) / Yeoh Keat Hoe - Yeoh, Keat Hoe (2014)
This research aims at improving the efficiency of solution processed organic light emitting diodes (OLEDs). The first part of this research work involved investigating the effects of Triton X-100 in a single layer solution processed blue phosphorescent OLED (PHOLED) with poly(vinylcarbazole) (PVK) and 1,3-bis[(4- tertbutylphenyl) -1,3,4 oxidiazolyl] phenylene (OXD-7) as host and bis(4,6- difluorophenylpyridinato-N,C2)picolinatoiridium (FIrpic) act as guest. Results indicate that the addition of Triton X-100 into the emissive layer (EML) can provide spatial separation between the guest-host which reduces the back energy transfer from the high triplet FIrpic to the low triplet PVK. The addition of Triton X-100 also increased the EML film roughness which is beneficial for electron injection at the cathode as evidenced from the Atomic Force Microcsopy (AFM) images, single carrier devices characteristics and photovoltaic measurements. Blue PHOLED with efficiency 8.5 lm/W at 1000 cd/m2 was achieved by adding Triton X-100 into the EML. This efficiency is comparable to the best efficiency of a single layer solution processed blue PHOLED reported to date. The effects of perfluorinated ionomer (PFI) doped poly(ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS) as hole injection layer (HIL) in a single layer solution processed blue PHOLED was investigated. A systematic study on the interplay of PFI concentrations, device efficiency, PEDOT:PSS thin film conductivity and transparency were carried out to determine the optimum amount of PFI to yield the best blue PHOLED efficiency. Compared to the control device, the optimized device efficiencies improved from 7.3 lm/W and 5.9 lm/W to 9.4 lm/W and 7.9 lm/W at 100 cd/m2 and 1000 cd/m2 respectively. We successfully demonstrated that the efficiency of a single layer solution processed yellow fluorescent OLED can be increased markedly by treating the EML surface with fluorinated alcohol. The fluorinated alcohol treatment improves the device efficiency to 19.3 lm/W at 1000 cd/m2 which corresponds to ~74% increment compared to the control device. To the best of our knowledge, this power efficiency is one of the best reported to date for a solution processed yellow fluorescent OLED. The improvement is attributed to the formation of a surface dipole layer induced by the fluorinated alcohol which effectively lowered the cathodic injection barrier. It was further shown that solvent with higher dipole moment is better in passivating traps on the EML surface. This could be another reason for the high efficiency yellow OLED achieved using fluorinated alcohol treatment. The final part of this research work involved the developments of high efficiency double layer solution processed blue PHOLED. The first emissive layer consists of PVK and FIrpic mixed with 4,4′,4″-tris(N-carbazolyl)-triphenylamine (TCTA) or OXD-7. The second layer consists of an alcohol-soluble 2,7- bis(diphenylphosphoryl)-9,9′-spirobi(fluorine) (SPPO13) and FIrpic. The incorporation of OXD-7 into PVK blurs the interface between the emissive layers heterojunction and widens the recombination zone while blending TCTA into PVK reduces the hole injection barrier from PEDOT:PSS to to the first emissive layer. The best blue device gave an acceptable power efficiency of 11 lm/W at 1000 cd/m2, which is comparable to the best reported fully solution processed multi layer blue PHOLED reported to date.